Poverty, Inequality, and Inclusive Growth in Asia 2010
DOI: 10.7135/upo9780857288066.015
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Segregation and Gender Discrimination in Labor Markets: Thailand and Viet Nam

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For the last decades there is no clear agreement on the tendency that the gender earnings gaps have followed. The overall difference shave narrowed but the unexplained component of the gap, overall, has not (Liu, 2001, 2003; Son, 2007). The results seem to show that it has reduced in some percentiles of the earnings distribution (Pham and Reilly, 2006).…”
Section: Introduction and Literature Reviewmentioning
confidence: 98%
“…For the last decades there is no clear agreement on the tendency that the gender earnings gaps have followed. The overall difference shave narrowed but the unexplained component of the gap, overall, has not (Liu, 2001, 2003; Son, 2007). The results seem to show that it has reduced in some percentiles of the earnings distribution (Pham and Reilly, 2006).…”
Section: Introduction and Literature Reviewmentioning
confidence: 98%
“…For the last decades there is no clear agreement on the tendency that the gender earnings gaps have followed. The overall difference shave narrowed but the unexplained component of the gap, overall, has not (Liu, 2001(Liu, , 2004Son, 2007). The results seem to show that it has reduced in some percentiles of the earnings distribution (Pham and Reilly, 2006).…”
Section: Introduction and Literature Reviewmentioning
confidence: 96%
“…The possible reasons that have been found to be associated to gender earnings disparities are sectorial segregation to lower wage sectors against female (Tzannatos, 1999), lower female supply along with wage structure (Blau and Kahn,2001), labor market institution and liberalization (Weichselbaumer et al, 2007;Blau and Kahn, 2001;Cornish, 2007 andTzannatos, 1999), and reduction on observed gender differences in characteristics such as education, experience, and geographical location (Son, 2007) among others. Education also plays an important role in explaining wage differentials (Ñopo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%